Boosting Direct X‐Ray Detection in Organic Thin Films by Small Molecules Tailoring. (2nd December 2018) - Ciavatti, Andrea; Basiricò, Laura; Fratelli, Ilaria; Lai, Stefano; Cosseddu, Piero; Bonfiglio, Annalisa; Anthony, John E.; Fraboni, Beatrice
Abstract: The attention focused on the application of organic electronics for the detection of ionizing radiation is rapidly growing among the international scientific community, due to the great potential of organic technology to enable large‐area conformable sensor panels. However, high‐energy photon absorption is challenging as organic materials are constituted of atoms with low atomic numbers. Here it is reported how, by synthesizing new solution‐processable organic molecules derived from 6, 13‐bis(triisopropylsilylethynyl)pentacene (TIPS‐pentacene) and 2, 8‐difluoro‐5, 11‐bis(triethylsilylethynyl)anthradithiophene, with Ge‐substitution in place of the Si atoms to increase the material atomic number, it is possible to boost the X‐ray detection performance of organic thin films on flexible plastic substrates. Bis(triisopropylgermylethynyl)‐pentacene based flexible organic thin film transistors show high electrical performance with higher mobility (0.4 cm 2 V −1 s −1 ) and enhanced X‐ray sensitivity, up to 9.0 × 10 5 µC Gy −1 cm −3, with respect to TIPS‐pentacene‐based detectors. Moreover, similar results are obtained for 5, 11‐bis(triethylgermylethynyl)anthradithiophene devices, confirming that the proposed strategy, that is, increasing the atomic number of organic molecules by chemical tailoring to improve X‐ray sensitivity, can be generalized to organic thin film detectors, combining high X‐ray absorption, mechanical flexibility, and large‐area processing. Abstract : The X‐ray detection performance of organic thin films on flexible plastic substrate is boosted by chemical tailoring of new solution‐processable organic molecules derived from 6, 13‐bis(triisopropylsilylethynyl)‐pentacene and 2, 8‐difluoro‐5, 11‐bis(triethylsilylethynyl)anthradithiophene, with Ge‐substitution in place of the Si atoms to increase the material atomic number.